Avaliação preliminar da qualidade das águas subterrâneas de dois municípios paraenses: subsídios à gestão hídrica na Região Metropolitana de Belém - OLIVEIRA, Lucas Cruz (2018)
In the counties of Belém and Benevides, both located in the metropolitan área of Belém (RMB), the captation of groundwater for water supply is a reality, since the waters of Bologna and Água Preta lakes are insufficient to supply the population's demand, and possible sources of surface water are contaminated by waste and sewage. This essay has the objective of preliminary evaluation of the quality of underground water in these counties, from the concentration of dissolved íons and physical-chemical parameters. The groundwater samples, proceeding from the aquifer Barreiras, were collected from wells of about 30 m depth in Benevides (Bela Água company and in a particular ranch) and in Belém (residencies in the neighbourhoods São Braz and Guamá). The hydrochemical parameters pH, temperature (T), electrical conductivity (EC), total dissolved solids (STD) were measured in situ with portable analyzer. The anionic composition (nitrate, phosphate, chloride, fluoride, sulfate) of the water was determined by liquid chromatography with conductivity detection in the Geosciences Institute. Temperatures ranged from 27.4 °C in Benevides to 28.9 ° C in Belém. It was observed an acid character of the samples (medium pH of 4.55 ± 0.77), common for the waters of the Barreiras system. STD and CE values ranged from 0.01 g / L to 0.31 g / L, and from 0.30 mS / cm to 0.64 mS / cm, respectively. Nitrate, sulfate, chloride and fluoride íons concentrations oscilled respectively from: 2.66 to 49.5; 0.15 to 29.9; 2.60 to 152.91; and 0.02 to 0.63. Phosphate was not detected by the chromatographic method. In general, the concentrations of the anions were higher in samples from Belém, exceptionally with the fluoride ion, which showed higher concentration in Benevides. Only the nitrate concentration reached a value higher than allowed by the CONAMA Resolution 396/2008 in Guamá. Circumstances such as disorganized urban occupation, a disability in the health system, a presence of cemeteries, among others make these shallow wells vulnerable to contamination, particularly in the Guamá neighborhood.